Pedagogia de projetos e formação humana integral: as contribuições dos projetos na Educação Profissional e Tecnológica - Silva Sobrinho, Moysés Hassan da (2022)
The present research was based on the need to discuss the relationship between the pedagogy of Projects and Integral Human Formation, seeking, in a systematic and critical way, to overcome the teaching-learning vision detached from a critical, inventive and committed formation with social transformation. Therefore, it was proposed to analyze the use of Project Pedagogy as an active methodology in the integral human formation of students, perceiving them as active subjects of their learning process. During the research, the main characteristics of the Pedagogy of Projects and its contributions to the formation of Integral Humanity are highlighted. For that, a case study of a 2nd year class of the Technical Course in Administration in the Integrated Form of the IFAM campus Coari was developed, in order to point out the discoveries made and the results achieved after the reflection and analysis of the process. Data collection was carried out through the application of questionnaires and semi structured interviews. The results had their data tabulated and submitted to the treatment of the Discursive Textual Analysis methodology, which indicate that the pedagogy of projects contributed significantly to the integral development of the students. As an educational product of this research, a Pedagogical Orientation Guide was developed for the use of project pedagogy in Vocational and Technological Education.